2007
DOI: 10.1097/01.anes.0000267605.40258.98
|View full text |Cite
|
Sign up to set email alerts
|

Oral Gabapentin Activates Spinal Cholinergic Circuits to Reduce Hypersensitivity after Peripheral Nerve Injury and Interacts Synergistically with Oral Donepezil

Abstract: Although gabapentin may relieve neuropathic pain by actions at many sites, these results suggest that its actions in the brain to cause spinal cholinergic activation predominate after oral administration. Side effects, particularly nausea, cannot be accurately determined on rats. Nevertheless, oral donepezil is well tolerated by patients in the treatment of Alzheimer dementia, and the current study provides the rationale for clinical study of combination of gabapentin and donepezil to treat neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 23 publications
(42 reference statements)
5
34
0
Order By: Relevance
“…Oral administration of the drug reached a maximum possible effect of 59%, in agreement with previous literature reports for this route of administration [Field et al, 1999;Fox et al, 2003;Reyes-García et al, 2004;Hayashida et al, 2007]. For spinal administration, gabapentin had a higher antiallodynic effect (67%) suggesting a significant spinal component in the antiallodynic effect of this drug, as previously established [Mixcoatl-Zecuatl et al, 2004;Yoon and Yaksh, 1999a;Coderre et al, 2005;Cheng and Chiou, 2006].…”
Section: Antiallodynic Effect Of Gabapentinsupporting
confidence: 90%
“…Oral administration of the drug reached a maximum possible effect of 59%, in agreement with previous literature reports for this route of administration [Field et al, 1999;Fox et al, 2003;Reyes-García et al, 2004;Hayashida et al, 2007]. For spinal administration, gabapentin had a higher antiallodynic effect (67%) suggesting a significant spinal component in the antiallodynic effect of this drug, as previously established [Mixcoatl-Zecuatl et al, 2004;Yoon and Yaksh, 1999a;Coderre et al, 2005;Cheng and Chiou, 2006].…”
Section: Antiallodynic Effect Of Gabapentinsupporting
confidence: 90%
“…The hypothesis is further supported by pre-clinical studies showing that the combination of gabapentin and donepezil produces synergistic effects on mechanical hypersensitivity in nerve-injured rats. 11,12 The present small-scale trial was obviously not designed to detect synergism in patients but to explore the clinical relevance of adding donepezil to existing gabapentin treatment by means of a mixedeffects statistical approach. Despite the small number of subjects in the study, this method was sensitive enough for detecting statistically significant differences between monotheraphy and combination therapy (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we and others have shown that the combination of gabapentin and the cholinesterase inhibitor donepezil produces synergism in nerve-injured rats. 11,12 The idea of using cholinergic drugs for analgesia is not a novel concept. 13 It is well known that acetylcholine is released in the spinal cord as a physiological response to noxious stimuli or in the immediate post-operative period, i.e., during a painful state.…”
mentioning
confidence: 99%
“…Oral gabapentin activates spinal cholinergic circuits to reduce hypersensitivity after peripheral nerve injury [131]. Several studies have shown that gabapentin and pregabalin are effective in reducing pain intensity, opioid consumption and opioid-related adverse effects after surgery [132,133].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%